(untitled) (Research, Society and Development, 2022)
The indiscriminate consumption of medicinal plants by the population can cause negative effects, since certain substances present can be toxic. Cróton L. species are often used in the form of infusions and teas in traditional medicine. The aim of this study was to evaluate the mutagenic, genotoxic and cytotoxic potential of Cróton spp. (Euphorbiaceae). The tests took place in meristematic cells of the Allium strain treated with different concentrations of fractions. In the analysis of the results, cytotoxic and mutagenic potentials were observed in Cróton betaceus and Cróton lundianus. Fractionation showed toxic effects in the species, such as the appearance of micronuclei, chromosome breaks and sprouts, bridges, multipolar anaphases, chromosome adhesions revealing possible harmful effects to humans, as well as reinforcing and elucidating that the use of medicinal plants must be carried out properly conscious and responsible because some plants have intoxication potential and must, therefore, be consumed with care and attention.